Revitalization of Soil Contaminated by Petroleum Products Using Materials That Improve the Physicochemical and Biochemical Properties of the Soil - Jadwiga Wyszkowska; Agata Borowik; Magdalena Zaborowska; Jan Kucharski (Molecules)
One of the key challenges in environmental protection is the reclamation of soils degraded by organic pollutants. Effective revitalization of such soils can contribute to improving the climate and the quality of feed and food, mainly by eliminating harmful substances from the food chain and by cultivating plants for energy purposes. To this end, research was carried out using two sorbents, vermiculite and agrobasalt, to detoxify soils contaminated with diesel oil and unleaded gasoline, using maize as an energy crop. The research was carried out in a pot experiment. The level of soil contamination with petroleum products was set at 8 cm3 and 16 cm3 kg−1 d.m. of soil, and the dose of the revitalizing substances, i.e., vermiculite and agrobasalt, was set at 10 g kg−1 of soil. Their effect was compared with uncontaminated soil and soil without sorbents. The obtained research results prove that both diesel oil and gasoline disrupt the growth and development of Zea mays. Diesel oil destabilized plant development more than gasoline. Both products distorted the activity of soil oxidoreductases and hydrolases, with diesel oil stimulating and gasoline inhibiting. The applied sorbents proved to be useful in the soil revitalization process, as they reduced the negative effects of pollutants on Zea mays, increased the activity of soil enzymes, enhanced the value of the biochemical soil quality indicator (BA), and improved the cation exchange capacity (CEC), the sum of exchangeable base cations (EBC), pH, and the Corg content. Agrobasalt demonstrated a greater potential for improving soil physicochemical properties, inducing an average increase in CEC and EBC values of 12% and 23%, respectively, in soil under G pressure, and by 16% and 25% in DO-contaminated soil.